Hydrodynamic loads acting on a circular porous plate horizontally submerged in waves. (15th May 2017) - Zhao, Fenfang; Zhang, Tongzheng; Wan, Rong; Huang, Liuyi; Wang, Xinxin; Bao, Weiguang
Abstract: The problem of a circular porous plate horizontally submerged in water is investigated within the context of linear potential theory. The porous plate is either fixed in monochromic waves or forced to oscillate in the heave or pitch mode in still water. Darcy's law is applied to give the boundary conditions on the porous plates. The boundary value problems are solved semi-analytically by means of the eigenfunction-expansion for multiple regions. Two approaches that have commonly been adopted in previous studies are both used in the present study. The hydrodynamic forces acting on the plates are evaluated. Comparisons are made between the results of these two methods and good agreement is observed. The effects of wave parameters, the submerged depth and the porosity of plates are discussed. The Haskind relation is examined and confirmed for the porous plate as well. Highlights: Two approaches are applied to solve the problem. The hydrodynamic forces are evaluated and compared by two methods. The Haskind relation is examined and confirmed for the porous plate.